Air and water stable germacarbonyl compounds. Issue 42 (12th October 2022) - Mahawar, Pritam; Shukla, Pratima; Chandra Joshi, Prakash; Singh, Dharmendra; Kumar, Hemant; Mukherjee, Goutam; Nagendran, Selvarajan
Abstract : Air and water stable germacarbonyl compounds are reported. Thio- 12 and selenogermaamide 13 react with CuX at ambient conditions to afford Cu(i ) complexes. Selective binding of 12 and 13 with CuCl and CuBr in a mixture of CuX is seen (X = Cl, Br, I). Abstract : Germacarbonyl compounds are the germanium analogs of carbonyl compounds requiring an inert atmosphere for stability. Making these compounds survive the ambient conditions was not feasible given the lability of the GeE bonds (E = O, S, Se, Te). However, the first examples of germacarbonyl compounds synthesized under ambient conditions by taking advantage of dipyrromethene ligand stabilization are detailed here; the isolated compounds are thiogermanone 3, selenogermanone 4, thiogermacarboxylic acid 6, selenogermacarboxylic acid 7, thiogermaester 9, selenogermaester 10, thiogermaamide 12, and selenogermaamide 13 with GeE bonds (E = S, Se). Compounds 12 and 13 can react under atmospheric conditions with copper(i ) halides offering air and water stable monomeric 14–15 and dimeric 16–19 copper(i ) complexes (halide = Cl, Br, I). Apart from just binding, selectivity was also observed; thiogermaamide 12 and selenogermaamide 13 bind CuCl and CuBr, respectively, when treated with a mixture of copper(i ) halides.